Prototype development of light weight aluminium matrix composite automotive brake rotor - Maleque, Md. Abdul; Wan Yusoff, Wan Ahmad Yusmawiza; Samat, Noorasikin; Ali, Mohammad Yeakub; Rahman, Md Mustafizur; Adetayo A., Adebisi (2017)
The global demand for light weight energy savings and high performance characteristic material has translated to the emergence of advance composite materials. Presently, cast iron is used for brake rotor production, however, due to higher density resulting more fuel consumption and emission of carbon dioxide making the environment unsafe. The recyclability of the cast iron is advantageous but the evolution of CO2 during re-melting has to be taken into consideration. In this prototype project, lightweight aluminium matrix composite (with the reinforcement of SiC) brake rotor was fabricated using simple and cost effective stir casting method. Actual car test was performed using Proton car with new developed prototype brake rotor. The wear performance test was conducted using universal wear and friction testing machine. The thermal distribution analysis was performed using both finite element (FE) simulation and actual car brake rotor test rig. The outcome of the new composite brake rotor achieved ~50% weight reduction and a corresponding energy savings of 19% when compared with cast iron brake rotor. The actual car test result showed uniform distribution of heat with minimum hot spot generation which revealed stable thermal performance due to better thermal diffusivity and coefficient of thermal expansion of the composite. Moreover, the wear performance exhibits superior resistance as a result of the formation of oxide layers during braking contact which serves as lubricant, thus prolonging service life of the new light weight composite brake rotor.